The Hegemon's Tool Kit : US Leadership and the Politics of the Nuclear Nonproliferation Regime - Gibbons, Rebecca Davis (Book collections on Project MUSE., 2022)
"Rebecca Davis Gibbons argues that the nuclear nonproliferation regime is a fundamental part of the US-led global ordering project, that Washington, DC, has long persuaded other states to join this regime such that a decline in US relative power could result in nuclear proliferation"--